2006
DOI: 10.1292/jvms.68.1211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Insulin Reaction of Peripheral Blood T Cells between Healthy Holstein Dairy Cows and JB during the Periparturient Period

Abstract: ABSTRACT. To compare the changes in the insulin reaction of Holstein dairy cows and Japanese Black cows (JB) during the periparturient period, the insulin resistance test in vivo and lymphocytes proliferation with insulin in vitro were performed. Ten healthy Holstein dairy cows (Holstein group) and 10 healthy JB cows (JB group) used in this study were observed on days 60, 40, and 20 before calving and days 7 and 20 after calving. In insulin resistance reaction in vivo and in vitro, a low insulin-stimulated glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The lower GH-R expression of the Weight Loss Group during month 2 might have been due to depression of lymphocyte response stimulated by PHA. Previous report have found that periparturie n t H o l s t e i n c o w s f r e q u e n t l y e x p e r i e n c e immunosuppression following reduction of glucose transport activity in T cells [18]. We doubtful that GH played a role in the immune system of the periparturient dairy cows preventing the occurrence of infectious disease.…”
Section: Cd45rmentioning
confidence: 85%
“…The lower GH-R expression of the Weight Loss Group during month 2 might have been due to depression of lymphocyte response stimulated by PHA. Previous report have found that periparturie n t H o l s t e i n c o w s f r e q u e n t l y e x p e r i e n c e immunosuppression following reduction of glucose transport activity in T cells [18]. We doubtful that GH played a role in the immune system of the periparturient dairy cows preventing the occurrence of infectious disease.…”
Section: Cd45rmentioning
confidence: 85%
“…The available disease-associated variables, mastitis, SCC above 100,000, retained placenta, metritis, and ketotic risk were used to exclude diseased cows, as these are known in uencing factors on milk yield (42,43). Parity, another known in uencing variable on milk yield and the periparturient cow's immune system (29,44,45) proved to be signi cant in univariable analysis of the present study. Thus, parity was reduced to primiparous cows.…”
Section: Statistical Analysesmentioning
confidence: 89%
“…The leukocyte fraction consists mainly of lymphocytes, macrophages, and neutrophils, and its concentration depends on diet, age, breed, and physiological and individual conditions [8,373,374]. For example, it has been shown that heifers have lower activity of colostral immune cells than cows with three or more lactations [375]. On the other hand, Kampen et al [376] found no significant effect of cow health status on colostral lymphocyte concentration.…”
Section: Cellsmentioning
confidence: 99%